1997
DOI: 10.1084/jem.186.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-driven C–C Chemokine-mediated HIV-1 Suppression by CD4+ T Cells from Exposed Uninfected Individuals Expressing the Wild-type CCR-5 Allele

Abstract: Despite repeated exposure to HIV-1, certain individuals remain persistently uninfected. Such exposed uninfected (EU) people show evidence of HIV-1–specific T cell immunity and, in rare cases, selective resistance to infection by macrophage-tropic strains of HIV-1. The latter has been associated with a 32–base pair deletion in the C–C chemokine receptor gene CCR-5, the major coreceptor of macrophage-tropic strains of HIV-1. We have undertaken an analysis of the HIV-specific T cell responses in 12 EU individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 21 publications
3
69
0
Order By: Relevance
“…It is significant that these T cells appear to be HIV antigen driven (they are specific for a conserved region of the HIV-1 Env), suggesting that these chemokine-producing helper cells could be part of the protective immune response [116]. In another cohort of exposed uninfected (EU) people wild-type for the CCR5 gene, Paxton et al show that CD4 ϩ cells from EU ϩ/ϩ individuals secrete high amounts of ␤-chemokines and have relatively lower surface expression of CCR5, which may explain the reduced infectability of EU cells [112].…”
Section: Chemokine/chemokine Receptor Axes In Aids Pathogenesis Chemomentioning
confidence: 99%
“…It is significant that these T cells appear to be HIV antigen driven (they are specific for a conserved region of the HIV-1 Env), suggesting that these chemokine-producing helper cells could be part of the protective immune response [116]. In another cohort of exposed uninfected (EU) people wild-type for the CCR5 gene, Paxton et al show that CD4 ϩ cells from EU ϩ/ϩ individuals secrete high amounts of ␤-chemokines and have relatively lower surface expression of CCR5, which may explain the reduced infectability of EU cells [112].…”
Section: Chemokine/chemokine Receptor Axes In Aids Pathogenesis Chemomentioning
confidence: 99%
“…Moreover, in a cohort of uninfected hemophiliacs, despite repeated exposure to contaminated blood products, protection has been associated with the ability of peripheral blood mononuclear cells (PBMCs) to produce higher levels of RANTES, MIP-1␣, and MIP-1␤ compared with hemophiliacs who were never treated with contaminated blood products (31). A specific immune response involving a high production of ␤ chemokines by CD4 ϩ T cells seems to play a role of protection in exposed uninfected individuals (32) and may contribute to the control of viral replication in long-term nonprogressors (33). Higher ␤-chemokine secretion by PBMCs has been described in nonprogressors compared with rapid progressors (34), and higher production of MIP-1␤ by PBMCs has been associated with an asymptomatic status and decreased risk of disease progression (35).…”
mentioning
confidence: 99%
“…Accordingly, there has been considerable interest in whether these chemokines impact natural HIV infection as a result of their ability to reduce cell surface CCR5 expression. Several studies have shown that activated peripheral blood mononuclear cells (PBMC) from HIV-exposed but uninfected individuals (26)(27)(28) and nonhuman primates protected from simian immunodeficiency virus challenge by certain vaccines (29-32) produced high levels of RANTES, MIP-1␣, and MIP-1␤. Other studies show an association between higher-production HIV-suppressive chemokines from activated PBMC and a more favorable clinical status in HIVϩ individuals (27,33,34).…”
mentioning
confidence: 99%